Law Enforcement Against Criminal Acts Of Cockfighting Gambling - Alvin Makale (Universitas Negeri Gorontalo, 2020)
This study aims to determine law enforcement against perpetrators of cockfighting gambling as a crime in the Gorontalo Regency area. The method used in this research is empirical or sociological research methodology. This study uses a qualitative approach and sampling using purposive sampling. The results of this study indicate that the process of law enforcement by the police against perpetrators of criminal acts of cockfighting gambling in the Gorontalo Regency area is carried out in two ways, namely first, pre-emptive law enforcement where in law enforcement the police take a persuasive approach to the community and provide direction on legal awareness in the environment. the community and also carry out mapping so that every crime event can be detected as early as possible. While the second law enforcement is repressive enforcement which is the final step taken by the Gorontalo Resort police to eradicate the practice of cockfighting gambling in Gorontalo Regency. This process consists of several stages; accept fights, investigations, investigations, arrests, confiscation of evidence, and detention. It is better not only to use the applicable criminal law as the overall solution, but also to take an integral or systemic approach. So, the effort to overcome this cockfighting gambling process must also be taken with a socio-cultural approach, a moralist approach, and a flexible educational approach to the current developments of society.